Characterizing Failure to Establish Hepatitis C Care of Baby Boomers Diagnosed in the Emergency Department. (4th October 2016) - Franco, Ricardo A.; Overton, E. Turner; Tamhane, Ashutosh R.; Forsythe, Jordan M.; Rodgers, Joel B.; Schexnayder, Julie K.; Guthrie, Deanne; Thogaripally, Suneetha; Zinski, Anne; Saag, Michael S.; Mugavero, Michael J.; Wang, Henry E.; et al.
Abstract: Background: Emergency departments (EDs) are high-yield sites for hepatitis C virus (HCV) screening, but data regarding linkage to care (LTC) determinants are limited. Methods: Between September 2013 and June 2014, 4371 baby boomers unaware of their HCV status presented to the University of Alabama at Birmingham ED and underwent opt-out screening. A linkage coordinator facilitated referrals for positive cases. Demographic data, International Classification of Diseases, Ninth Revision codes, and clinic visits were collected, and patients were (retrospectively) followed up until February 2015. Linkage to care was defined as an HCV clinic visit within the hospital system. Results: Overall, 332 baby boomers had reactive HCV antibody and detectable plasma ribonucleic acid. The mean age was 57.3 years (standard deviation = 4.8); 70% were male and 61% were African Americans. Substance abuse (37%) and psychiatric diagnoses (30%) were prevalent; 9% were identified with cirrhosis. During a median follow-up of 433 days (interquartile range, 354–500), 117 (35%) linked to care and 48% needed inpatient care. In multivariable analysis, the odds of LTC failure were significantly higher for white males (adjusted odds ratio [aOR], 2.57; 95% confidence interval [CI], 1.03–6.38) and uninsured individuals (aOR, 5.16; 95% CI, 1.43–18.63) and lower for patients with cirrhosis (aOR, 0.36; 95% CI, 0.14–0.92) and access to primary care (aOR, 0.20; 95% CI, 0.10–0.41). Conclusions: In this cohort of baby boomers with newly diagnosed HCV in the ED, only 1 in 3 were linked to HCV care. Although awareness of HCV diagnosis remains important, intensive strategies to improve LTC and access to curative therapy for diagnosed individuals are needed.